Updated perspectives on the cytosolic sulfotransferases (SULTs) and SULT-mediated sulfation. Issue 1 (2nd January 2017) - Suiko, Masahito; Kurogi, Katsuhisa; Hashiguchi, Takuyu; Sakakibara, Yoichi; Liu, Ming-Cheh
Abstract: The cytosolic sulfotransferases (SULTs) are Phase II detoxifying enzymes that mediate the sulfate conjugation of numerous xenobiotic molecules. While the research on the SULTs has lagged behind the research on Phase I cytochrome P-450 enzymes and other Phase II conjugating enzymes, it has gained more momentum in recent years. This review aims to summarize information obtained in several fronts of the research on the SULTs, including the range of the SULTs in different life forms, concerted actions of the SULTs and other Phase II enzymes, insights into the structure–function relationships of the SULTs, regulation of SULT expression and activity, developmental expression of SULTs, as well as the use of a zebrafish model for studying the developmental pharmacology/toxicology. Graphical abstract: : The cytosolic sulfotransferases (SULTs) are Phase II detoxifying enzymes that mediate the sulfate conjugation of numerous xenobiotic molecules.